Curvature in Biological Systems: Its Quantification, Emergence, and Implications across the Scales. Issue 13 (15th February 2023) - Schamberger, Barbara; Ziege, Ricardo; Anselme, Karine; Ben Amar, Martine; Bykowski, Michał; Castro, André P. G.; Cipitria, Amaia; Coles, Rhoslyn A.; Dimova, Rumiana; Eder, Michaela; Ehrig, Sebastian; Escudero, Luis M.; et al.
Abstract: Surface curvature both emerges from, and influences the behavior of, living objects at length scales ranging from cell membranes to single cells to tissues and organs. The relevance of surface curvature in biology is supported by numerous experimental and theoretical investigations in recent years. In this review, first, a brief introduction to the key ideas of surface curvature in the context of biological systems is given and the challenges that arise when measuring surface curvature are discussed. Giving an overview of the emergence of curvature in biological systems, its significance at different length scales becomes apparent. On the other hand, summarizing current findings also shows that both single cells and entire cell sheets, tissues or organisms respond to curvature by modulating their shape and their migration behavior. Finally, the interplay between the distribution of morphogens or micro‐organisms and the emergence of curvature across length scales is addressed with examples demonstrating these key mechanistic principles of morphogenesis. Overall, this review highlights that curved interfaces are not merely a passive by‐product of the chemical, biological, and mechanical processes but that curvature acts also as a signal that co‐determines these processes. Abstract : Curvature as a local descriptor for shape has been revealed to play a fundamental role in the development of biological systems. Advanced 3D characterization methods allow its quantification across time and length scales indicating that cells and tissue growth can cause emergence of curved surfaces but in turn curvature also acts as a trigger for specific biological processes.